2019
DOI: 10.1098/rsta.2018.0224
|View full text |Cite
|
Sign up to set email alerts
|

Strong magnetic exchange and frustrated ferrimagnetic order in a weberite-type inorganic–organic hybrid fluoride

Abstract: We combine powder neutron diffraction, magnetometry and 57 Fe Mössbauer spectrometry to determine the nuclear and magnetic structures of a strongly interacting weberite-type inorganic–organic hybrid fluoride, Fe 2 F 5 (H taz ). In this structure, Fe 2+ and Fe 3+ cations form magnetically frustrated hexagonal tungsten bronze layers of corner-sharing octahedra. Our powde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…That does not mean that the investigation of ferrimagnets, in general, is not an active field. The contrary is the case [22][23][24][25][26][27][28][29]. In this publication, we use with the time-dependent cluster mean-field theory (t-CMFT) a quantum-mechanical method to describe the ferrimagnetic J 1 -J 2 model.…”
Section: Introductionmentioning
confidence: 99%
“…That does not mean that the investigation of ferrimagnets, in general, is not an active field. The contrary is the case [22][23][24][25][26][27][28][29]. In this publication, we use with the time-dependent cluster mean-field theory (t-CMFT) a quantum-mechanical method to describe the ferrimagnetic J 1 -J 2 model.…”
Section: Introductionmentioning
confidence: 99%
“…Two additional important differences are the replacement of two F atoms by water molecules and the absence of A cations (Figure ). ,, Both weberites and inverse weberites have been investigated to understand the concept of coupled magnetic frustration in compositions where two types of cations occupy distinct crystallographic sites. ,,,, In the 1980s, Laligant et al successfully synthesized M II Fe III F 5 (H 2 O) 2 (M II = Fe, Mn, Co, Ni, Zn) using solvothermal methods and their studies indicated that in inverse weberites frustrated magnetism can be induced when both M II and M III have unpaired electrons. ,,, However, frustrated magnetism properties were studied only for Fe 3+ -based compounds, and those of other inverse weberite structures have not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…My own group's contribution to the issue is an example of a phase transition under pressure, illustrating how host-guest hydrogen bonding-a unique feature in coordination frameworks compared to their mineral analogues-can stabilize particular crystallographic structures [25]. The articles from the groups of Clark [26] and of Saines [27] both consider magnetic frustration in different framework topologies. Magnetic exchange is among the subtlest and most variable features of coordination frameworks, and these articles demonstrate the variety of magnetic order and disorder that can be achieved even in apparently analogous materials.…”
Section: Introductionmentioning
confidence: 99%